Sistem sočasne proizvodnje toplote in električne energije z visokotemperaturnimi gorivnimi celicami s protonsko prevodnimi membranami - Lotrič, Andrej (visokošolska dela, 2017)
In the thesis, a concept of a small portable power unit with an integrated methanol steam reformer (MSR) and a high-temperature proton exchange membrane fuel cell (HT PEMFC) stack has been developed. A reactor was designed to use a highly active state-of-the-art MSR catalyst. Based on experimental data, gathered by measurements of individual characteristics of the MSR and the HT PEMFC stack, an innovative hybrid numerical model was developed which was used to calculate mass and energy flows and the efficiency of the integrated system. Experimental and numerical results confirm the feasibility of the autothermic energy system. Guidelines for the construction of the prototype integrated system are presented.
Keywords: Disertacije; dissertations; energy systems modeling; fuel cells; fuel processor methanol steam reforming; gorivna celica; Gorivne celice; heat integrated system; modeliranje energetskega sistema; parni reforming metanola; procesor goriva; proton exchange membrane; protonsko prevodna membrana; toplotno integriran sistem